2023
DOI: 10.3847/2041-8213/ad0da8
|View full text |Cite
|
Sign up to set email alerts
|

The Preexplosion Environments and the Progenitor of SN 2023ixf from the Hobby–Eberly Telescope Dark Energy Experiment (HETDEX)

Chenxu Liu,
Xinlei Chen,
Xinzhong Er
et al.

Abstract: Supernova (SN) 2023ixf was discovered on 2023 May 19. The host galaxy, M101, was observed by the Hobby–Eberly Telescope Dark Energy Experiment collaboration over the period 2020 April 30–2020 July 10, using the Visible Integral-field Replicable Unit Spectrograph (3470 ≲ λ ≲ 5540 Å) on the 10 m Hobby–Eberly Telescope. The fiber filling factor within ±30″ of SN 2023ixf is 80% with a spatial resolution of 1″. The r < 5.″5 surroundings are 100% covered. This allows us to analyze the spatially resolved preexplos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The HETVIPS spectra can also provide a way to classify a number of supernova objects found by photometric surveys, as shown in Vinkó et al (2023). Finally, Liu et al (2023) illustrated that VIRUS spectra can also be used to investigate the spatially resolved pre-explosion local environments of known supernovae.…”
Section: Science Casesmentioning
confidence: 95%
“…The HETVIPS spectra can also provide a way to classify a number of supernova objects found by photometric surveys, as shown in Vinkó et al (2023). Finally, Liu et al (2023) illustrated that VIRUS spectra can also be used to investigate the spatially resolved pre-explosion local environments of known supernovae.…”
Section: Science Casesmentioning
confidence: 95%
“…The foreground extinction from the Milky Way in the line of sight of SN 2023ixf is E(B − V ) MW =0.008 mag (Schlegel et al 1998;Schlafly & Finkbeiner 2011). For the host galaxy extinction, we used the result of Liu et al (2023) obtained by analyzing the spectral data from the Hobby Eberly Telescope Dark Energy Experiment, who obtained an extinction value of E(B − V ) host = 0.06 ± 0.14 mag that is slightly larger than E(B − V ) = 0.031 mag given by some previous works (Smith et al 2023;Teja et al 2023). Using the extinction law of Cardelli et al (1989) and assuming R V = 3.1, we obtain the extinction values of 0.338, 0.316, 0.221, 0.183, 0.117, and 0.095 mag accounting for both the Milky Way and host galaxy for the uvgriz bands, respectively.…”
Section: Multiband Photometric Observations and Data Reductionmentioning
confidence: 99%
“…In addition to the SN 2023ixf itself, the currently available photometric information pointed to a luminous red supergiant with a dense shell of circumstellar material as its progenitor candidate (Jencson et al 2023;Kilpatrick et al 2023;Liu et al 2023;Xiang et al 2023). The progenitor has been estimated to have a bolometric luminosity of L ∼ (10 4.7 -10 5.4 ) L e , an effective temperature of T eff ∼ (3200-3900) K, and a mass of M ∼ (9-20) M e (Hosseinzadeh et al 2023;Jencson et al 2023;Kilpatrick et al 2023;Neustadt et al 2023;Niu et al 2023;Pledger & Shara 2023;Soraisam et al 2023;Xiang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the direct detection of SNe II-P progenitors has been possible in a few dozen cases thanks to highresolution images from space-and ground-based facilities (see, e.g., Smartt 2009Smartt , 2015Tartaglia et al 2017;Van Dyk 2017). Several studies of the SN 2023ixf progenitor were made due to its proximity to the Earth (Dong et al 2023;Jencson et al 2023;Kilpatrick et al 2023;Liu et al 2023;Niu et al 2023;Panjkov et al 2023;Pledger & Shara 2023;Soraisam et al 2023;Bersten et al 2024;Neustadt et al 2024;Ransome et al 2024;Van Dyk et al 2024). As the RSG progenitors have a large mass range (Eldridge et al 2017;Davies & Beasor 2020), any new possible identification is important to better constrain the mass limit.…”
Section: Possible Progenitor Of Sn 2024ggimentioning
confidence: 99%
“…The isochrones that match the measurement best have an age of ∼10 (red) or 15 (green) Myr, with an initial mass of 17 or 14 M e and a metallicity of Z = 0.025 or Z = 0.01. In different studies, the progenitor of SN 2023ixf has been identified as an RSG with an estimated mass range between ∼9 and 22, e.g., 17 ± 4 M e (Jencson et al 2023), 11 ± 2 M e (Kilpatrick et al 2023), 20-22 M e (Liu et al 2023), 8-10 M e (Pledger & Shara 2023), 20 ± 4 M e (Soraisam et al 2023), 9-14 M e (Neustadt et al 2024), 14-20 M e , (Ransome et al 2024), and 12-14 M e (Van Dyk et al 2024). This indicates that the progenitor of SN 2024ggi was a moderately massive star.…”
Section: Possible Progenitor Of Sn 2024ggimentioning
confidence: 99%